2008
DOI: 10.1007/s11089-008-0134-1
|View full text |Cite
|
Sign up to set email alerts
|

Well-being and Spirituality from a Korean Perspective: Based on the Study of Culture and Subjective Well-being

Abstract: Criteria for well-being and spirituality are culturally bound. In this article, therefore, the notions of well-being and spirituality were reconsidered from a Korean perspective. Two major conceptual approaches that pertain to "subjective well-being" research in social psychology provide the methodological framework for this study. While "bottom-up" approaches focus on how external events and situations influence happiness, "top-down" approaches center on diverse variables within an individual and his or her c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 16 publications
1
8
0
1
Order By: Relevance
“…Contrary to most Western societies, in which spirituality is often placed in a personal domain, Indonesians practice religious values to improve social connectedness and to fulfill the expectations of others (Yeo, 2014). This finding is parallel with that of Kwon (2008), who indicates that spirituality is expressed in different ways in the United States compared to Korea due to different cultural perspectives. All of these cultural traits are likely to have an influence on the way people perceive well‐being as including factors associated with it.…”
Section: Discussionsupporting
confidence: 85%
“…Contrary to most Western societies, in which spirituality is often placed in a personal domain, Indonesians practice religious values to improve social connectedness and to fulfill the expectations of others (Yeo, 2014). This finding is parallel with that of Kwon (2008), who indicates that spirituality is expressed in different ways in the United States compared to Korea due to different cultural perspectives. All of these cultural traits are likely to have an influence on the way people perceive well‐being as including factors associated with it.…”
Section: Discussionsupporting
confidence: 85%
“…One specific element of culture that differentiates individualists from collectivists is the value placed on feelings as information (Kwon, 2008). As reported, in individualistic culture, ability to feel and express feelings is emotionally relieving and contributes to a sense of well-being.…”
Section: International Journal Of Research Studies In Psychology 39mentioning
confidence: 99%
“…Filipinos have a propensity for indirect communication. Another differentiating cultural factor cited by Kwon (2008) is the regard for standards of normative behaviour. On this particular point, East Asian cultures are inclined toward adherence to these norms.…”
Section: International Journal Of Research Studies In Psychology 39mentioning
confidence: 99%
“…Some psychologists have taken the fact of cultural variance to imply that there is the universal notion of well-being (Ryan and Deci, 2001). Social psychologists recognized that, because of cultural differences, people's behavior and subsequent outcomes can vary from culture to culture and thus, particular research on well-being cannot be applied to every individual and every culture (Kwon, 2008). Any study of well-being, however, needs to diversify its sampling of cultures (Kim-Prieto and Eid, 2004).…”
Section: Psychological Well-being and Culturementioning
confidence: 99%
“…On the other hand, Yamamoto and Wallhagen (2002) reported that to describe the state of psychological well-being, the Japanese often use the word ikigai which refers to 1) specific experience that creates a sense of worth and happiness, 2) the resultant cognitive evaluation that finds one's life meaningful because of the experience, and 3) the sense of fulfillment and joy that is derived from the cognitive evaluation. Kwon (2008) referred to major conflicting criteria in evaluation of one perspective of well-being for East Asians, in the recognition of standards of normative behavior: East Asian culture identifies with collectivism, and people in a collectivist culture develop "other-focused" emotions such as shame and sympathy. Yamamoto and Wallhagen (2002) referred to The Japanese Self as characterized by its emphasis on situationality and relativity, in order to maintain harmony in interpersonal relationships, where the presentational self becomes situation-specific and relational to the interactants.…”
Section: Psychological Well-being and Culturementioning
confidence: 99%